2021
DOI: 10.3390/antiox10121857
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and Zeaxanthin Distribution in the Healthy Macula and Its Association with Various Demographic Factors Examined in Pseudophakic Eyes

Abstract: The macular pigment consisting of lutein (L) and zeaxanthin (Z) protects photoreceptors via its antioxidative and barrier activities. This study aimed to determine L and Z distribution in the healthy macula and their association with various demographic factors. Macular pigment optical density (MPOD) was measured using fundus autofluorescence spectroscopy in 352 pseudophakic eyes with no fundus diseases. Pseudophakia was chosen to avoid the influence of cataract in the measurement of fundus autofluorescence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Concerning ophthalmology, lutein accumulates in the macula, acting as a filter for harmful blue light and helping to protect the eye from oxidative damage [ 192 ]. Lutein also acts via antioxidative and barrier properties to protect the retina photoreceptors, as seen in the work of Obana et al [ 193 ]. It has been shown to reduce the risk of age-related macular degeneration, glaucoma, cataracts, and other eye diseases [ 178 , 194 , 195 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning ophthalmology, lutein accumulates in the macula, acting as a filter for harmful blue light and helping to protect the eye from oxidative damage [ 192 ]. Lutein also acts via antioxidative and barrier properties to protect the retina photoreceptors, as seen in the work of Obana et al [ 193 ]. It has been shown to reduce the risk of age-related macular degeneration, glaucoma, cataracts, and other eye diseases [ 178 , 194 , 195 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following a standardized protocol will allow researchers to contribute to a shared population-level database to establish reference points and compare findings from different studies. Additionally, future research studies may consider reporting about nutrient supplement usage, as previous intervention studies reported a significant and consistent increase in RS-based SCS in adults after taking high doses of lutein and zeaxanthin supplements [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…AREDS2 also demonstrated that including lutein and zeaxanthin in the antioxidant mixture brings about a greater benefit than having no carotenoids or β-carotene. It is thought that lutein, zeaxanthin, α-tocopherol, and ascorbate can exert their beneficial effect by scavenging lipid-derived free radicals and superoxide and, in the case of lutein and zeaxanthin, by quenching of singlet oxygen and excited states of photosensitizers as well as by absorption of blue light in the innermost layers of the retina in the centre of the macula, thereby preventing blue light reaching POS and RPE in this area [ 38 , 39 , 68 , 69 , 120 ]. The results of this study demonstrate that the scavenging of retinoid cation radicals can be added to the repertoire of antioxidant actions of AREDS2 antioxidants.…”
Section: Discussionmentioning
confidence: 99%